2021
DOI: 10.3390/nu13041054
|View full text |Cite
|
Sign up to set email alerts
|

Response to Malnutrition Treatment in Low Weight-for-Age Children: Secondary Analyses of Children 6–59 Months in the ComPAS Cluster Randomized Controlled Trial

Abstract: Weight-for-age z-score (WAZ) is not currently an admission criterion to therapeutic feeding programs, and children with low WAZ at high risk of mortality may not be admitted. We conducted a secondary analysis of RCT data to assess response to treatment according to WAZ and mid-upper arm circumference (MUAC) and type of feeding protocol given: a simplified, combined protocol for severe and moderate acute malnutrition (SAM and MAM) vs. standard care that treats SAM and MAM, separately. Children with a moderately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…This study showed that simplified, combined treatment of children with acute malnutrition can be effective in a routine care setting as observed in this rural Sahelian context where a total of 27 601 children were admitted to the treatment program over a period of over 3 years. All programmatic indicators exceeded the SPHERE standards [48] in all subgroups previously identified as potentially more vulnerable or less responsive to treatment [5,9,28,29] including children with concurrent wasting and stunting, children with high weight at admission and older children. Treatment provided by CHWs resulted in similarly high recovery as when treatment was provided at the health facility level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study showed that simplified, combined treatment of children with acute malnutrition can be effective in a routine care setting as observed in this rural Sahelian context where a total of 27 601 children were admitted to the treatment program over a period of over 3 years. All programmatic indicators exceeded the SPHERE standards [48] in all subgroups previously identified as potentially more vulnerable or less responsive to treatment [5,9,28,29] including children with concurrent wasting and stunting, children with high weight at admission and older children. Treatment provided by CHWs resulted in similarly high recovery as when treatment was provided at the health facility level.…”
Section: Discussionmentioning
confidence: 99%
“…Certain sub-groups have been previously identified as potentially responding less well to treatment [4,5,9,29,52] or generally more at risk of mortality [53,54]. Those include children with SAM by both criteria [4,5], children with severely low WHZ or MUAC [52], children with concurrent wasting and stunting [29,53,54], girls [5,55] and young children [5,9,52,56].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…the targeting of malnourished children with the greatest risk of mortality (Bailey et al, 2021;Myatt et al, 2018). However, as low WAZ is not currently used at admission or routinely monitored during wasting treatment, little is known about how this group of children respond to either therapeutic or supplementary treatment protocols.…”
Section: Key Messagesmentioning
confidence: 99%